Implementasi Metode VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) dalam Pengambilan Keputusan Penerima Bantuan Langsung Tunai Dana Desa di Daerah Pesisir (Studi Kasus : Pengujan, Bintan) - Cut Putri Khairani; Nola Ritha; Nurul Hayaty (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2023)
Inappropriate distribution of assistance is one of the problems often encountered in the provision of social assistance program benefits, such as the Village Fund Cash Assistance (BLT-DD) in Pengujan Village. There are still some people who are marked as recipients of direct cash assistance but not in accordance with the predetermined criteria. This research implements a decision support system method with the VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method in making decisions on BLT-DD recipients. The VIKOR method selects and ranks alternatives based on conflicting criteria. In this method, alternatives are evaluated based on all the criteria set, choosing a solution that is close to the ideal. This research involved analyzing 200 community data in Pengujan Village, Bintan. The criteria evaluated included age, occupation, income, dependents, house type & status, fishing needs, fishing vehicle, history of illness, disability, and history of receiving assistance. The testing methods used in this research include user acceptance testing, precision, recall, and accuracy. Testing was carried out through filling out questionnaires and using desktop devices, involving 10 respondents from village officials and neighborhood associations in Pengujan Village. Based on the analysis conducted, the test results with a precision value of 71%, recall of 71%, and accuracy of 94%. In addition, user acceptance testing also achieved a feasibility value of 88%.